Acrosternum heegeri Fieber, 1861 (Hemiptera: Heteroptera: Pentatomidae), another Mediterranean bug expanding to the north - Károlyi, Balázs; Rédei, Dávid (Zootaxa, 2017)
Acrosternum heegeri Fieber, 1861 (Hemiptera: Heteropera: Pentatomidae: Pentatominae: Pentatomini), a Holomediterranean-Turanian shield bug species, is recorded for the first time from Hungary, representing the first known occurrence of the species in Central Europe. The species is illustrated, its geographic distribution is reviewed. The occurrence of A. heegeri in two localities in Budapest, regular records from one of the localities in the years 2015 and 2016, and the finding of an overwintering individual indicate the presence of a stable population in the city; the species is probably already established and it is locally abundant. Its further spread in Europe is expected.